INFLUENCE OF NURSES' PHYSICAL AND MENTAL WORKLOAD WITH THE IMPLEMENTATION OF THE TEAM METHOD IN ISKANDAR MUDA LEVEL IV HOSPITAL INPATITION ROOM 07. 01 LHOKSEUMAWE - Eridha Putra; Gadis Halizasia; Maulida; Nurul Khairi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Nursing as professional service or care has the characteristics and tips of nursing, is oriented towards other objective needs, refers to professional nursing standards and uses nursing ethics as a general requirement. The aim of this research is to determine the effect of nurses' physical and mental workload by implementing the team method. This research uses quantitative research with a correlational design with a cross sectional approach. This research was carried out on July 31 to August 11, 2023.The population is90 nurses. The total sample was 73 respondents. The sampling technique used purposive sampling. Data analysis in this study used the chi square test, based on the results of the research conducted in the Inpatient Room of Level IV Iskandar Muda Hospital 07.01 Lhokseumawe, research conducted on 73 respondents, it can be seen that there is heavy physical workload in application of the team method with a p value of 0.013 < 0.05,which means there is a relationship between physical workload in the application of the team method And mental workload in application of the team method with a p value of 0.029 < 0.05,which means there is a relationship between mental workload in implementing the team method. It is recommended that hospital management provide education and training regarding occupational health safety on a regular basis, form a team that controls physical factors and work conditions, and provide counseling institutions/services for nursing staff.